ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MASYARAKAT MENGGUNAKAN LAYANAN BANK DIGITAL (Studi pada masyarakat kabupaten bone) - Anthi, Dina Hadry; Andi Patimbangi; Muh. Hasbi Ash Shiddiq (Program Studi Manajemen Keuangan Syariah, 2025)
The rapid development of information technology in the current digital era has influenced human behavior patterns in accessing various information and various service features, especially in digital banking. The purpose of this study is to analyze the factors that influence the interest of the Bone Regency community in using digital banking services with the Technology Acceptance Model (TAM) approach. This study analyzed 50 respondents using quantitative methods. The data collection technique was the distribution of questionnaires via Google Form, then the data analysis technique used multiple regression tests. The results of this study indicate that there is a positive and significant influence of the variables of perceived ease and perceived benefits on people's interest in using digital banking services.